Decentralized and cost-effective solar water purification system for remote communities. (May 2018) - Abd-ur-Rehman, Hafiz M.; Shakir, Sehar; Atta-ur-Razaq,; Saqib, Hamza; Tahir, Saad
Abstract: In this study, a modified stepped solar still is proposed for water desalination. The overall objective of this work is to develop and test the proposed still design to identify the productivity enhancement as compared to conventional basin type solar still. The proposed design takes the advantage of its stepped configuration that allows the water stream to maintain a minimum desirable water column height and the water flow through the stages under the force of gravity. A minimum water depth in the still results in a higher rate of evaporation. The still is also incorporated with Fresnel lens to increase the water temperature that eventually increases the rate of water evaporation. Another important aspect of this design is the incorporation of phase-change-material (PCM) to increase the operational hours of the solar still. Consequently, daily productivity of fresh water is increased.